Interdependence, Incarnation, and Disability in Charlotte Yonge's The Pillars of the House - Hingston, Kylee-Anne (2018)
The author suggests that aspects of recent disability models and disability theology were already in the Victorian consciousness, doing so by applying narrative theory and literary analysis to demonstrate how Charlotte Yonge's (1871-1873) novel The Pillars of The House manifests inclusive disability theology via its structural and narrative depiction of incarnational interdependence. The novel's interdependent, multiple-focus plots emphasize the novel's theological themes of incarnation in the Church as many members of one body. This thematic emphasis in the novel relies on a resymbolization of the cross that reflects the incontrovertible interdependence of people, both with and without disabilities. This meaning is then reiterated through the interdependent daily lives of the novel's disabled and nondisabled characters, and through sacramental theology conveyed in scenes in which characters with disabilities receive sacraments.
Keywords: Disability; Disability Studies; Family; Inclusion; Religion